Legal Analysis of the Crime of Sexual Exploitation of Children Case Study of Decision Number 109Pid.Sus2024PN.Jkt.Sel - Biochandra Hutapea; Hotman Sinambela; Mardiman Sane; Appe Hutauruk; Fendi Maruba Parlindungan Hutahaean (International Journal of Science and Environment (IJSE), 2026)
The crime of sexual exploitation of children is a serious crime that violates the dignity, honor, and human rights of children as part of the nation's future generation. Children are a vulnerable group that requires special legal protection, as emphasized in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. This study aims to analyze the legal regulations regarding the crime of sexual exploitation of children, the application of the law in Decision Number 109/Pid.Sus/2024/PN.Jkt.Sel, as well as obstacles and solutions in law enforcement in Indonesia. The research method used is normative juridical with a statutory and case approach. Data were obtained through a literature study of laws and regulations, legal literature, and analysis of court decisions that are the object of the study. The results of the study indicate that the crime of sexual exploitation of children has been expressly regulated in Article 76D and Article 76E in conjunction with Article 76E. Article 81 and Article 82 of the Child Protection Law, with a maximum prison sentence of 15 years and a maximum fine of IDR 5,000,000,000. In Decision Number 109/Pid.Sus/2024/PN.Jkt.Sel, the Panel of Judges declared the defendant legally and convincingly proven to have committed sexual exploitation of children, thus imposing a prison sentence in accordance with applicable provisions. The judge's considerations were based on evidence in the form of witness statements, victim statements, evidence, and the defendant's statement that were mutually consistent, in accordance with the evidentiary system in the Criminal Procedure Code (KUHAP). The conclusion of this study is that the application of the Child Protection Law in cases of sexual exploitation of children has been carried out in accordance with the provisions, although in practice there are still obstacles, such as limited psychological assistance for victims, lack of public understanding, and cultural factors that often make victims reluctant to report.